Peran Tradisi Gotong Royong dalam Membangun Komunikasi yang Harmonis di Desa Kesugihan Kecamatan Pulung - Ahmad Yusry Nasrullah; Dyan Putri Ayu (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Gotong royong is an Indonesian tradition that has been preserved since before Indonesia's independence. Along with the times, the tradition of gotong royong is threatened with extinction by the younger generation who are tech-savvy. However, gotong royong in Kesugihan village has been instilled from an early age. Gotong royong has become a necessity for individuals, groups and all residents of Kesugihan village. This study aims to determine the role of gotong royong in building harmonious communication in Kesugihan village. This type of research is qualitative with a qualitative descriptive approach. The service method used is the Participatory action research (PAR) method where the author acts as a participant among Kesugihan villagers in playing an active role in carrying out gotong royong activities. The results of the research obtained that Kesugihan still preserves the culture of gotong royong starting from small children, teenagers, adults to the elderly. Gotong royong plays a positive role to build harmonious communication in Kesugihan village.